Chapter Is Induced Abortion a Part of Family Planning in China - Englert, Yvon (InTechOpen, 2020)
Family planning policy is one of the basic policies in China. Since the founding of New China, it has gone through three stages during its development process, which include free fertility policy, one-child policy (including selective two-child policy), and universal two-child policy. The number of induced abortions in China has increased from 3,910,110 in 1971 to 9,626,731 in 2017, and the proportion of induced abortions in birth control surgeries of family planning in China has increased from 30.0% in 1971 to 50.6% in 2017. It is concluded that although induced abortion is not a part of the family planning policy of China, it has been a part of family planning services in China.